2002
DOI: 10.1897/1551-5028(2002)021<1922:aactoz>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Toxicity of Zinc to the Mottled Sculpin Cottus Bairdi

Abstract: The acute and chronic toxicity of zinc to wild mottled sculpin (Cottus bairdi) was measured with 13-d and 30-d flow-through toxicity tests, respectively. Exposure water hardness was 48.6 mg/L as CaCO3 and 46.3 mg/L as CaCO3 in the acute and chronic tests, respectively; pH was slightly above neutral; and temperature near 12 degrees C. The median lethal concentration (LC50) after 96 h was 156 microg Zn/L, but decreased with exposure duration to a median incipient lethal level (ILL50) of 38 microg Zn/L after 9 d,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 3 publications
4
19
0
Order By: Relevance
“…Our BLM-normalized copper acute value for mottled sculpins ranked ninth out of 28 listed aquatic taxa, and our chronic value ranked second of 13 taxa. This finding is consistent with results of previous toxicity tests with mottled sculpins collected from the White River in Colorado [20,21]. Results of our tests indicate that current recommended WQC for cadmium, copper, and zinc adequately protect rainbow trout but may not adequately protect mottled sculpins.…”
Section: Sensitivity Of Mottled Sculpins Relative To Other Taxa and Wsupporting
confidence: 88%
See 2 more Smart Citations
“…Our BLM-normalized copper acute value for mottled sculpins ranked ninth out of 28 listed aquatic taxa, and our chronic value ranked second of 13 taxa. This finding is consistent with results of previous toxicity tests with mottled sculpins collected from the White River in Colorado [20,21]. Results of our tests indicate that current recommended WQC for cadmium, copper, and zinc adequately protect rainbow trout but may not adequately protect mottled sculpins.…”
Section: Sensitivity Of Mottled Sculpins Relative To Other Taxa and Wsupporting
confidence: 88%
“…The inconsistent results of previous toxicity tests with sculpins may be due in part to differences in the age and size of the sculpins tested. Woodling et al [20] and Brinkman and Woodling [21] reported that mortality of mottled sculpins exposed to zinc continued well past the typical 96-h test period for acute toxicity tests. Differences in test duration also may have affected results Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hardness, conductivity, and dissolved zinc levels at the collection site were 240 mg/L as CaCO 3 , 454 μs/cm, and <10 μg Zn/L, respectively. The fish were collected, transported, received, and maintained at the Colorado Division of Wildlife Toxicology Laboratory in Fort Collins, Colorado, USA, as previously described [3]. After a 26‐d holding period, well water was added to dechlorinated Fort Collins municipal tap water to increase the water hardness to 150 mg/L as CaCO 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Existing U.S. Environmental Protection Agency (U.S. EPA) criteria and various stream restoration objectives may not be adequate to protect diverse aquatic communities if sculpin are more sensitive to zinc than trout species. Laboratory tests demonstrated the mottled sculpin, Cottus bairdi , was extremely sensitive to zinc in soft water [3]. Sensitive species must be protected to ensure that appropriate water quality criteria and restoration objectives are chosen for zinc‐contaminated stream reaches.…”
Section: Introductionmentioning
confidence: 99%